The Impact of Advertising on Social Networking Sites on Consumers' Attitudes Towards the Brand - Mstaffa, Dr. Abdulkhaliq I.; Saeed, Shilan T. (Mitanni Journal of Humanitarian Sciences, 2023)
Abstract: Thise study aims to identify the most important effects of socila media advertising on consumers attitudes in Kurdistan region, the study is considered a descriptive study and the media survey method was used, the study community includes all consumers of telecommunications company services in the Kurdistan region consisting of companies (Asiasel, Cork Telecom and Zain), and university professors in the region were selected as the intended sample of the study to measure the potential impacts of electronic advertising, and the researcher relied on the questionnaire form as a key tool for collecting information and distributed ( 380) questionnaire form (paper and electronic) on the sample of the study. One of the most important findings of the study is that social media advertising greatly affects the attention and interest of the buyers and enhances their purchase intention for the services of their preferred telecommunications companies and brand.